Cultural Play at a Distance: Post-COVID Serious Heritage Games - Susannah Emery; Erik Malcolm Champion (Heritage, 2025)
The COVID-19 pandemic introduced new challenges for the Galleries, Libraries, Archives, and Museums (GLAM) sector, including drastically reduced visitation, constrained funding, and pressure to increase the amount and richness of digital rather than physical interaction. The authors draw upon explorative projects to examine the potential of serious games, augmented and virtual reality, and community-led design to address GLAM sector challenges raised by COVID-19. The initial findings suggest that while digital heritage projects often suffer from limited interactivity and accessibility, participatory game design and low-cost XR (extended reality) tools can enhance engagement and learning. The article concludes that open-ended, collaborative, and context-aware game frameworks offer a promising path for GLAM institutions to sustain relevance, support digital literacy, and adapt to post-pandemic challenges.